Impact of Fintech on Financial Stability of Small and Medium-Sized Business in Kingdom of Saudi Arabia. - Rahim, Adeel; Bangash, Romana; Khan, Hanana; Khan, Faisal (Transnational Press London Ltd., 2024)
The current study analyze impact of FinTech, on financial stability of Kingdom of Saudi Arabia growth inhibitors and obstacles for small and medium-sized businesses. Agriculture, industry, FinTech and services make up the sample's three primary industries. The convenience sample technique was used to identify a much higher percentage of SMEs. The expansion of SME is hampered by a number of problems. The study used Principal Component Analysis, a multivariate statistical technique, to identify the most and least important reasons impeding these businesses' expansion and development in Kingdom of Saudi Arabia. Long wait times for loan approval, a lack of collateral, corruption, and management-related challenges are found to be the main factors preventing SMEs in this region from succeeding more. The study identified a wide range of internal and external variables. Based on the findings from the empirical investigation and survey data, the report also makes a number of policy recommendations for regulatory agencies, lending institutions, and SME sector companies.